1999
DOI: 10.1063/1.371281
|View full text |Cite
|
Sign up to set email alerts
|

Hetero- and homoepitaxial Nd3+-doped LaF3 thin films grown by molecular beam epitaxy: A spectroscopic study

Abstract: Hetero- and homoepitaxial Nd3+-doped LaF3 thin films have been grown by molecular beam epitaxy. Two different orientations of CaF2 substrates, (111) and (110), have been used for the heteroepitaxial structures. High-resolution emission and excitation spectra as well as the decay time of the emission have been measured. The spectroscopic measurements demonstrate that one Nd3+ site is present in the LaF3 layers grown on CaF2(111) substrates but two slightly different Nd3+ centers are resolved in the films on CaF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The Nd-doping level was chosen to be 1 at.%, corresponding to LaF and NdF cell temperatures of 1165 C and 993 C, respectively. In previous work, we have reported high-resolution excitation spectroscopy, emission spectroscopy, and lifetime measurements on hetero-and homoepitaxial layers in order to determine the influence of the substrate on the crystal quality and the influence of the Nd doping level on spectroscopic properties [18]. It was found that the highest luminescence intensity is obtained in the samples doped with 1 at.% Nd.…”
Section: Thin-film Fabrication and Characterizationmentioning
confidence: 99%
“…The Nd-doping level was chosen to be 1 at.%, corresponding to LaF and NdF cell temperatures of 1165 C and 993 C, respectively. In previous work, we have reported high-resolution excitation spectroscopy, emission spectroscopy, and lifetime measurements on hetero-and homoepitaxial layers in order to determine the influence of the substrate on the crystal quality and the influence of the Nd doping level on spectroscopic properties [18]. It was found that the highest luminescence intensity is obtained in the samples doped with 1 at.% Nd.…”
Section: Thin-film Fabrication and Characterizationmentioning
confidence: 99%
“…This is consistent with other reports in the literature in which homoepitaxial designs in thin films have led to spectroscopic changes such as decreased inhomogeneous broadening in the luminescence. 35 In our case, the observed enhancement with similar factors at all emission wavelengths can be attributed to the reduced surface defects in addition to a possible additional energy transfer from Yb 3+ ions in the shell layer to the luminescent Tm 3+ ions in the core. By comparison, XRD data of the inert shell confirms an altered crystal field around luminescent Tm ions in the core through its effect on enlarged hexagonal lattice parameters and even eliminated tensile strain.…”
Section: Resultsmentioning
confidence: 99%
“…We have identified, by growing layers with different thicknesses, that the two centers in the films grown on the ͑110͒ substrate are not specifically associated with the layer-substrate interface, but both present throughout the thickness of the film. 6 The luminescence decay curves are mainly nonexponential at a short-time range and exponential at long times for all the samples. Figure 5 gives the results for the decay times of Fig.…”
Section: B Emission Properties With Respect To Substrate Concentratmentioning
confidence: 86%
“…Furthermore, two inequivalent Nd 3ϩ sites can be identified from a careful study of the emission and excitation spectra for the layers grown on the ͑110͒ face of CaF 2 . 6 The arrows in Fig. 4 indicate the positions of the transition 4 F 3/2 (1)→ 4 I 11/2 (1) for the two centers.…”
Section: B Emission Properties With Respect To Substrate Concentratmentioning
confidence: 99%
See 1 more Smart Citation